Comparative Analysis of Six Phase Induction Motor - Sarıgül, İsmail; Özdemir, Mehmet (My University, 2021)
In recent years, AC induction motors have replaced DC motor. The most important reason for this is that DC motors have a mechanical brush and commutator system that is subject to wear and tear over time. While DC motor drivers need a lot of maintenance due to this system, induction motors do not require almost any maintenance since this system is not available. In recent years, technological advances in the field of multiphase induction motors have led to a significant evolution. A lot of research has been done around the world and a lot of new and interesting developments have been reported to the literature. This paper provides information about six-phase induction. In addition, what kind of advantages the concept of multiphase provides and how this structure is formed contains information about them. The six-phase induction motor will be simulated through the MATLAB/SIMULINK package program and compare with three-phase induction motor. Both motors were run in simulation using the same parameters. At the end of the simulation, current, moment and speed graphs of the six-phase induction motor and three-phase induction motor will be drawn according to time. The study also included equations used during modeling and equivalent circuits belonging to a six-phase induction motor. It has been graphically shown that a six-phase induction motor is more advantageous than a three- phase motor. For example, in six-phase induction motors, the transition time to a continuous state is shorter. In addition, while the frequency of torque vibration increases, its amplitude decreases, the current value of each phase decreases, the stator copper losses are less than the three-phase induction motor. In motors, usually the power needed is divided by the number of phases. So the more phases there are, the greater the power carrying capacity. Today, multi-phase induction motor drives are used in special applications such as electric vehicles, space technology, aerospace applications, as moving power on ships, electric trains, which require high reliability and power.
Keywords: Induction motor Six phase d-q model Simulation Three phase